Tantangan Implementasi Kurikulum Pendidikan IPS Di Era Globalisasi - Izza Lathifah; Hodri Fungkiuudin; Rizqi Trisnaningtyas; Rizky Yus Setiawan; Nilna Afifatul Alfiyah; Lailatul Muthoharoh; Nafi’ur Rohman (Concept: Journal of Social Humanities and Education, 2023)
This study aims to assess the challenges faced in implementing the Social Sciences (IPS) curriculum in the era of globalization. Employing a literature review methodology, it gathers and analyzes data from academic publications, educational policy reports, and case studies related to the IPS curriculum. The findings suggest that the current IPS curriculum needs to integrate contemporary global issues and utilize educational technology to enhance student engagement and understanding. The study also identifies an urgent need for teacher professional development to teach methods that meet the needs of 21st-century students. Furthermore, the study recommends strategies to strengthen students' critical and analytical skills in responding to global dynamics. The main conclusions emphasize the importance of collaboration between educational institutions and policymakers in designing and implementing an adaptive and sustainable curriculum.